2020
DOI: 10.1177/1687814020924893
|View full text |Cite
|
Sign up to set email alerts
|

A review on the thermal performance of nanofluid inside circular tube with twisted tape inserts

Abstract: Working fluid with higher thermal conductivity and tube with better fluid mixing are two crucial elements for heat transfer enhancement in heat exchanger system. Hence, several methods and techniques have been explored to improve heat transfer efficiency, including dispersing nanoparticles into conventional heat transfer fluid and inserting instruments inside the tube of the heat exchanger. Studies have shown that nanofluid can improve heat transfer efficiency of the system due to its higher thermal conductivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 105 publications
(130 reference statements)
0
9
0
Order By: Relevance
“…Twisted short-length tape out-performs full-length-TT in terms of continuous pumping power. TT can be used to increase heat transmission by creating the heatexchangers with laminar flow [5], [25].…”
Section: Insert Tape Twisted When the Flow Is Laminarmentioning
confidence: 99%
See 1 more Smart Citation
“…Twisted short-length tape out-performs full-length-TT in terms of continuous pumping power. TT can be used to increase heat transmission by creating the heatexchangers with laminar flow [5], [25].…”
Section: Insert Tape Twisted When the Flow Is Laminarmentioning
confidence: 99%
“…Because of the rising consciousness for power savings, many researchers have been involved in HT enhancement, because an enlargement in HT rate leads to expanded machine performance [3], [4], this is a requirement for all thermal application systems. HT improvement methodology is categorized into several classes: compound, active, and passive [5]. [6] Experimentally studied the effect of Twisted Tape (TT) in laminar flow.…”
Section: Introductionmentioning
confidence: 99%
“…In order to prepare the nano-fluid with a volume concentration of 0.02, with an average diameter of 30 nm and a purity of 99.99% for CuO, TiO2 was used. The mass of the required nanoparticles that is proportional to the specific volumetric concentration is first calculated using the following equation [14].…”
Section: Nano-fluidmentioning
confidence: 99%
“…The thermophysical properties of pure H2O, various base fluids and various nanoparticles which are heat capacity, density, effective dynamic viscosity; effective thermal conductivity and thermal expansion coefficient are given in Table 2. The following equations are used to calculate the density, specific heat, viscosity, and thermal conductivity of the TiO2/H2O and CuO/H2O nanofluid is produced by [15]:…”
Section: Nano-fluid Thermophysical Propertiesmentioning
confidence: 99%
“…In a laminar flow regime (Recr=2000), they observed that in a mass flow rate of 26.3 kg/s for flue gas and 111.6 kg/s coolant fluid at 1% volume concentration of copper nanofluid in the ethylene glycol base fluid, 9.5% increase was observed in the overall heat transfer coefficient of the nanofluid in comparison with the ethylene glycol base fluid. Ahmad et al (2020) carried out a review on the thermal performance of nanofluid inside circular tube with twisted tape inserts. They summarized 109 of journals from recent research on heat transfer enhancement of nanofluid flowing inside the tube with inserts as well as discussing the significant parameters that affected the system's efficiency such as nanoparticles' volume fraction, Reynolds number and types and configurations of inserts.…”
Section: Introductionmentioning
confidence: 99%